2016
DOI: 10.1620/tjem.240.1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma TGF-<i>β</i>1 Levels Are Elevated in Down Syndrome Infants with Transient Abnormal Myelopoiesis

Abstract: Infants with Down syndrome (DS) are at risk of developing a transient myeloproliferative disorder during the neonatal period, known as transient abnormal myelopoiesis (TAM). It is characterized by clonal myeloproliferation and is typically self-limiting. However, TAM can be a life-threatening disorder, when complicated by liver fibrosis. Here, we evaluated cytokine profiles in two male DS infants having TAM with or without liver dysfunction. The first patient, Patient 1, had hyperleukocytosis with cholestatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Moreover, TGF-β regulates the development and functionality of innate cells (dendritic cells, macrophages, granulocytes, and natural killer cells) and the peripheral tolerance against self-antigens [47]. In DS, increased TGF-β levels have been previously associated with transient abnormal myelopoiesis and complications of this condition [48] and pointed as a candidate biomarker for prenatal diagnosis [49].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TGF-β regulates the development and functionality of innate cells (dendritic cells, macrophages, granulocytes, and natural killer cells) and the peripheral tolerance against self-antigens [47]. In DS, increased TGF-β levels have been previously associated with transient abnormal myelopoiesis and complications of this condition [48] and pointed as a candidate biomarker for prenatal diagnosis [49].…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor (TGF)-β1 is a likely candidate involved in liver fibrogenesis of TAM (Arai et al 1999). And recently Maeda reported that IL-8 was associated with TAM with liver fibrosis (Maeda et al 2016). But these reports did not refer about the association between DS and pericardial effusion.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Se estima que entre el 5 % y el 30 % de los neonatos con SD desarrollan MAT, la cual es un trastorno de origen clónico caracterizado por megacarioblastos circulantes y cambios displásicos en las células de sangre periférica. [4][5][6] L a M A T a s o c i a d a a S D ( M A T -S D ) e s t á predispuesta por mutaciones en el gen del factor de transcripción hematopoyético GATA1 y solo se observa junto con la trisomía 21. 3 En la mayoría de los casos, la MAT se resuelve de manera espontánea; sin embargo, la producción de citocinas y la hiperviscosidad, debidas al aumento de blastos y la disfunción inmunológica, causan diversas afecciones.…”
Section: Introductionunclassified